Prevalence of prehypertension and hypertension in rural area of Amravati District of Maharashtra, India - Wasnik, Vinod R.; Jawarkar, Ajay K. (International Journal of Research in Medical Sciences, 2016)
Background: Hypertension is responsible for 57% of stroke deaths and 24% of coronary heart disease deaths in India. Cardiovascular disease will be the largest cause of death and disability in India by 2020. Hypertension is emerging as a major health problem. The prevalence of hypertension has increased in rural people. The objectives were to find the prevalence of prehypertension and hypertension in rural area of Amravati District and to study association between various factors and hypertension in a rural area. Methods: A community based cross sectional study was carried out in rural community. 792 study subjects aged 10 years and above were selected using systematic random sampling. A structured pretested schedule was used to collect data regarding demographic characteristics and blood pressure pattern. Mean, Standard Deviation, Chi- square test and ANOVA were used to analyze data. Results: The prevalence of prehypertension and hypertension was found to be 55.8% and 13.4% respectively. The mean systolic as well as diastolic blood pressure patterns were found to be higher with the increase in age. Older age and increased body mass index were significantly higher among hypertensive compared to normotensive. Factors like tobacco use and alcohol were significantly associated with hypertension. Conclusions: The prevalence of prehypertension and hypertension was found to be high in rural Amravati.